2019
DOI: 10.1002/art.40827
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Analytics of the Gut Microbiota in Patients With Juvenile Idiopathic Arthritis: A Longitudinal Observational Cohort Study

Abstract: Objective To assess the composition of gut microbiota in Italian and Dutch patients with juvenile idiopathic arthritis ( JIA ) at baseline, with inactive disease, and with persistent activity compared to healthy controls. Methods In a multicenter, prospective, observational cohort study, fecal samples were collected at baseline from 78 Italian and 21 Dutch treatment‐naive JIA patients with <6 months of disease durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 53 publications
7
50
3
1
Order By: Relevance
“…However, when comparing baseline samples with paired inactive disease samples, no differences in relative abundance were found. This finding may indicate that the gut microbiota profile is specific to the individuals with JIA, rather than the disease activity status …”
Section: Role Of Microbiota and Efficacy Of Therapeutics In Jiamentioning
confidence: 96%
See 1 more Smart Citation
“…However, when comparing baseline samples with paired inactive disease samples, no differences in relative abundance were found. This finding may indicate that the gut microbiota profile is specific to the individuals with JIA, rather than the disease activity status …”
Section: Role Of Microbiota and Efficacy Of Therapeutics In Jiamentioning
confidence: 96%
“…This finding may indicate that the gut microbiota profile is specific to the individuals with JIA, rather than the disease activity status. 90 Microbiota as JIA therapy response biomarkers Regarding the effect of pharmacological therapies on gut microbiota of patients with JIA, one of the first studies to describe potentially significant associations considered a group of patients with JIA-ERA treated with NSAIDs, alone or associated with sulfasalazine/methotrexate/biologics in different combinations, and a group of patients with JIA-non ERA, mainly treated with biologic drugs, such as etanercept and abatacept. Despite the low number of patients stratified by pharmacological treatment, authors observed enrichment in Collinsella (Actinobacteria), associated with exacerbation of joint disease, in patients with JIA-ERA treated with combined NSAIDs and sulfasalazine therapy.…”
Section: Microbiota and Jia Susceptibilitymentioning
confidence: 99%
“…Finally, in the most extensive study of its kind to date, van Dijkhuizen et al obtained fecal microbiota on a total of 99 treatment‐naive and newly diagnosed Italian and Dutch subjects and 107 local controls. As with the study by Di Paola et al, this study used the Roche 454 pyrosequencing device.…”
Section: Microbiota Alterations In Jiamentioning
confidence: 99%
“…A second organism that has emerged in these studies is the Ruminococcaceae family, which was increased in the ERA and in the polyarticular JIA patients in the Di Paola study as well as in the Italian patients in the van Dijkhuizen study . While this was not further speciated, one might speculate as to whether this was Ruminococcus gnavus , which was increased in two cohorts of patients with SpA and correlated with disease activity among those with concomitant inflammatory bowel diseases (IBD) .…”
Section: Microbiota Alterations In Jiamentioning
confidence: 99%
See 1 more Smart Citation